First report of Digitonthophagus gazella (Fabricius, 1787) and new records for Euoniticellus intermedius (Reiche, 1849) (Coleoptera: Scarabaeidae Latreille, 1802) in El Salvador - Pablo-Cea, José D.; Velado-Cano, Maryory A.; Fuentes, René; Cruz, Melvin; Ari Noriega, Jorge (Instituto de Ecología, A.C., 2018)
The presence of the beetle Digitonthophagus gazella (Fabricius, 1787) is reported for the first time. In addition, the range of distribution of Euoniticellus intermedius (Reiche, 1849) in El Salvador is expanded, based on information obtained from collections made over twelve years and the current distribution map of E. intermedius in the territory is presented. In addition, the current situation of both species in the country and Central America is briefly discussed.